2016
DOI: 10.1166/sam.2016.2651
|View full text |Cite
|
Sign up to set email alerts
|

<I>Ab Initio</I> Calculations of the Structural, Electronic and Elastic Properties of the <I>MZ</I>N<SUB>2</SUB> (<I>M</I> = Be, Mg; <I>Z</I> = C, Si) Chalcopyrite Semiconductors

Abstract: Four ternary semiconductors with the chalcopyrite structure (BeCN 2 , BeSiN 2 , MgCN 2 , and MgSiN 2 ) were studied using the first principles methods. The structural, electronic, optical and elastic properties were calculated. All these materials were found to be the indirect band gap semiconductors, with the calculated band gaps in the range from 3.46 eV to 3.88 eV. Comparison of the degree of covalency/ionicity of the chemical bonds in these compounds was performed. Anisotropy of the optical properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The detailed band gap values for each structure are given in Table . From Table , the calculated band gap values are basically consistent with the research results of others, , which also indicates the rationality of the electronic property calculation in this study. It can also be found that for MCN 2 (M = Be, Mg, Ca, Sr, Ba) compounds, the band gap value decreases with the increase of the metal atomic number.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The detailed band gap values for each structure are given in Table . From Table , the calculated band gap values are basically consistent with the research results of others, , which also indicates the rationality of the electronic property calculation in this study. It can also be found that for MCN 2 (M = Be, Mg, Ca, Sr, Ba) compounds, the band gap value decreases with the increase of the metal atomic number.…”
Section: Resultssupporting
confidence: 89%
“…This article also provides the cell parameters of the optimized MSiN 2 (M = Be, Mg, Ca, Sr, Ba) structure. The calculation results are shown in Table , and the calculated cell parameters are in good agreement with the research results of others. , …”
Section: Resultssupporting
confidence: 86%
“…Various chalcopyrite crystals were studied theoretically by us in the past. [70][71][72][73][74][75][76][77] Two representatives of this class of compounds were considered in the present paper: CuGaS 2 and CuInS 2 . In the chosen CuGaS 2 and CuInS 2 crystals each metal cation is four-fold coordinated by the sulfur anions; each sulfur anion is also four-fold coordinated by the metal cations [by two copper and two gallium (indium) ions].…”
Section: First-principles Calculations Of Physical Pressure Effects O...mentioning
confidence: 99%
“…Previous studies are either based on pure chalcopyritic compounds [22][23][24][25][26][27][28] or treat solid solutions for a select few possible elemental compositions [29]. Anyway, a comprehensive analysis of chalcopyritic solid solutions to our knowledge was not yet performed and certain data points are lacking.…”
Section: Introductionmentioning
confidence: 99%